Literasi Media Digital Pada Anak-Anak Majelis Talim Hidayatul Mubtadiin - Sagiyanto, Asriyani; Lancia, Ferrari; Liliyana, Liliyana; Syahlani, Achmad (LPPM Universitas Bina Sarana Informatika, 2021)
Digital media literacy is “the ability to access, analyze, evaluate and communicate content from media messages. Digital media literacy also means the ability to understand, analyze, and deconstruct media imagery. The ability to do this is aimed at making viewers as consumers of mass media - including children become aware or literate about the way media is constructed / made and accessed. In short, this literacy is often called